2020
DOI: 10.1159/000504693
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in T3 and T4b Breast Cancer Patients: Analysis in a Tertiary Cancer Hospital and Systematic Literature Review

Abstract: <b><i>Introduction:</i></b> Breast cancer represents the most common type of cancer among women in the world. The presence and extent of axillary lymph node involvement represent an important prognostic factor. Sentinel lymph node biopsy (SLNB) is currently accepted for T1 and T2 with negative axillae (N0); however, many patients with T3-T4b tumors with N0 are often submitted to unnecessarily axillary lymph node dissection. <b><i>Materials and Methods:</i></b> Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We found 2 studies that demonstrated the feasibility of SLNB in patients with T3/T4b breast cancer. One was a retrospective study conducted by de Oliveira et al, 11 involving 73 patients with T3/T4b breast cancer. They found that the identification rate of SLNB was 100%, and 60.3% of the patients did not have macrometastasis in the sentinel lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 2 studies that demonstrated the feasibility of SLNB in patients with T3/T4b breast cancer. One was a retrospective study conducted by de Oliveira et al, 11 involving 73 patients with T3/T4b breast cancer. They found that the identification rate of SLNB was 100%, and 60.3% of the patients did not have macrometastasis in the sentinel lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Although 2 studies had shown that SLNB is feasible in T3/T4b patients with breast cancer, but none of them reported survival results after SLNB. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…Вторая часть работы заключалась в анализе данных литературы, которые показали, что при размерах первичной опухоли, соответствующих Т3, частота N0-статуса составила 32,1 %, а при Т4b -61,0 %. Таким образом, авторы сделали вывод о том, что проведение БСЛУ может быть эффективным и помогает избежать излишней подмышечной лимфаденэктомии даже у пациентов с достаточно крупной первичной опухолью, классифицирующейся как Т3 или Т4b [11].…”
Section: проведение биопсии сторожевого лимфатического узла при разме...unclassified